AN ANALYSIS AND DESIGN OF APPLIANCE SERVER PROTOTYPE IN MIDDLE INDUSTRY - Santyadiputra, Gede Saindra (JST (Jurnal Sains dan Teknologi), 2016)
This is an initial research about development of appliance server prototype for middle industry. The main objective of this study is to analyze and design an alternative server as a solution to providing server device on a small industry. The prorotype used by small industry to implement their information system applications. This study uses ADDIE development method. ADDIE phase that has been used is analysis, design, and some evaluation of them (ADE). The result of analyze is user needs analysis, hardware requirements analysis and software requirement analysis. The result of design is network topology design, hardware architecture design, validation test instrument, feasibility testing instrument, performance testing instrument, evaluation of prototype feasibility instrument and evaluation of server performance instrument. In the future, the result of this study can be used as reference for development and implementation of appliance server in middle industry.